The importance of integrated implementation of lean construction and bim for improving the sustainability of construction projects - Marques, Luís P. (2015)
The implementation of Lean thinking in construction companies has gained a recognized space in the building industry. Based on the pillars of respect for people and continuous improvement, Lean Construction's main objectives are the reduction of waste and customer satisfaction, across the value chain. These pillars and objectives are the guide and the guarantee for improving the sustainability of construction projects. Presenting itself as an integrated process built on coordinated and reliable information, BIM provides more efficient collaborative process between different actors. This allows the creation of coordinated documentation, accurate views, performance reviews of buildings, estimated costs and construction times with more safety, speed, economy and reduced environmental impacts, ensuring higher levels of sustainability. The integrated implementation of Lean Construction philosophy and BIM methodology adds a second order value, not achievable otherwise.